Peran Strategis Indonesia dalam Meningkatkan Keamanan Maritim di Kawasan Asia Tenggara - Qhirani Aulia Rahman Latunrung; Imam Fadhil Nugraha (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Maritime security is a strategic issue in Southeast Asia due to the high dependence of ASEAN countries on sea lanes for trade and regional stability. This study aims to analyze Indonesia's role in strengthening maritime security cooperation in ASEAN. The methods used are literature studies and analysis of policy documents related to ASEAN maritime cooperation and national maritime policies. The results of the study show that Indonesia is active in various regional forums such as the ASEAN Maritime Forum (AMF) and the Expanded ASEAN Maritime Forum (EAMF), and carries the Global Maritime Fulcrum (GMF) initiative. Despite challenges such as overlapping institutional authority and limited resources, Indonesia continues to demonstrate a strong commitment to promoting maritime diplomacy, strengthening governance, and handling issues such as IUU Fishing and the South China Sea conflict. The implications of this cooperation are increased regional stability and strengthening ASEAN's position in facing the geopolitical dynamics of the Indo-Pacific.